The Problem of the Imagination of Eros. Theoretical Questions and Trajectories of Contemporary Lithuanian Poetry - Puskunigytė, Edita (Colloquia, 2026)
e arch for poetic language and by broader processes in culture, philosophy, and literary history. It raises the following questions: What does the imagination of eros mean? What is the phenomenological validity of the concept? What is distinctive about the representation of the imagination of eros in contemporary Lithuanian poetry? The theories of Maurice Merleau-Ponty, Jean-Paul Sartre, Wolfgang Iser, and other thinkers not only make it possible to delve more deeply into the essence of the phenomena of eros and imagination and substantiate an understanding about the phenomena that are characteristic of poetry, but also to create the conditions for conceptualizing the imagination of eros. The article looks into the poems of Sigitas Geda, Sigitas Parulskis, Gytis Norvilas and other authors, in which the experience of desire, erotic longing, bodily attraction, and physical as well as spiritual yearning is re-created by using a distinctive language of poetic imagery and metaphors. It also shows how this experience emerges through the prism of the imagination of the lyrical subject and the Other.
Keywords: eros; imagination; body; contemporary Lithuanian poetry